2020
DOI: 10.1038/s12276-020-0483-0
|View full text |Cite
|
Sign up to set email alerts
|

Liver progenitor cell-driven liver regeneration

Abstract: The liver is a highly regenerative organ, but its regenerative capacity is compromised in severe liver diseases. Hepatocyte-driven liver regeneration that involves the proliferation of preexisting hepatocytes is a primary regeneration mode. On the other hand, liver progenitor cell (LPC)-driven liver regeneration that involves dedifferentiation of biliary epithelial cells or hepatocytes into LPCs, LPC proliferation, and subsequent differentiation of LPCs into hepatocytes is a secondary mode. This secondary mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 115 publications
(192 reference statements)
1
50
0
Order By: Relevance
“…Several years ago, a population of oval cells located in the canals of Hering was described, and it was thought that they participate in regenerating the liver when it is severely damaged. Now, lineage tracing techniques have revealed that BECs dedifferentiate into liver progenitor cells (LPCs), which are none other than the oval cells, and then, they differentiate into hepatocytes (So et al, 2020). This mechanism is known as LPC-driven liver regeneration.…”
Section: From Phenotypic Fidelity To Cell Plasticity In the Livermentioning
confidence: 99%
“…Several years ago, a population of oval cells located in the canals of Hering was described, and it was thought that they participate in regenerating the liver when it is severely damaged. Now, lineage tracing techniques have revealed that BECs dedifferentiate into liver progenitor cells (LPCs), which are none other than the oval cells, and then, they differentiate into hepatocytes (So et al, 2020). This mechanism is known as LPC-driven liver regeneration.…”
Section: From Phenotypic Fidelity To Cell Plasticity In the Livermentioning
confidence: 99%
“…Liver injury can also trigger cholangiocyte proliferation and expansion in the liver parenchyma, a process known as ductular reaction (Roskams et al, 2004). Importantly, cholangiocytes can de-differentiate in vivo into bipotent liver progenitors that give rise to both hepatocytes and cholangiocytes (Itoh and Miyajima, 2014;Ko et al, 2020;So et al, 2020). The role of cholangiocytes in liver regeneration has been extensively debated.…”
Section: Hepatocytes and Cholangiocytes Exhibit Remarkable Plasticitymentioning
confidence: 99%
“…Hepatocyte-driven liver regeneration that involves the proliferation of pre-existing hepatocytes is a primary regeneration mode. Another mode is liver progenitor cell (LPC)-driven and involves dedifferentiation of biliary epithelial cells or hepatocytes into LPCs [ 48 ].…”
Section: Metabolite Supply For Liver Function and Energy Supply Fomentioning
confidence: 99%